Booms, busts, and normal times in the housing market - Agnello, Luca (2015)
We assess the existence of duration dependence in the likelihood of an end in housing booms, busts, and normal times. Using data for 20 industrial countries and a continuous-time Weibull duration model, we find evidence of positive duration dependence suggesting that housing market cycles have become longer over the last decades. Then, we extend the baseline Weibull model and allow for the presence of a change-point in the duration dependence parameter.We show that positive duration dependence is present in booms and busts that last less than 26 quarters, but that does not seem to be the case for longer phases of the housing market cycle. For normal times, no evidence of change-points is found. Finally, the empirical findings uncover positive duration dependence in housing market booms of European and non-European countries and housing busts of European countries. In addition, they reveal that while housing booms have similar length in European and non-European countries, housing busts are typically shorter in European countries.